Nursing students’ perceptions and experiences of student–lecturer evaluation as a strategy for improving teaching and learning at the University of Namibia - Ritu K. Stanislaus; Daniel O. Ashipala; Julia Amadhila (Curationis, 2026)
Background: In higher education, the student–lecturer evaluation (SLE) system is a critical mechanism for enhancing teaching quality and fostering student-centred learning. Despite its importance, limited research exists in Namibia on students’ perceptions and experiences of this evaluation process, particularly regarding its effectiveness in improving teaching and learning outcomes. Objectives: The study aimed to explore and describe nursing students’ perceptions and experiences regarding the SLE system at the Rundu Campus of the University of Namibia (UNAM). Method: A qualitative, explorative, descriptive and contextual design was employed. Fifteen students were purposively selected to participate in the study. Data were collected through semi-structured interviews, which were audio-recorded and transcribed verbatim. Thematic analysis was used to analyse the data and identify emerging themes and sub-themes. Results: Three main themes and nine subthemes were identified from the data analysis. This study explored nursing students’ perceptions and experiences regarding the use of SLE as a strategy for improving teaching and learning at the UNAM. Participants highlighted both the benefits and challenges of SLE, including its potential to improve teaching quality, as well as barriers such as lack of feedback, fear of reprisal, poor communication, late notifications and limited transparency. Conclusion: The study concluded that while SLEs have significant potential to improve teaching and learning, their effectiveness is constrained by administrative, logistical and communication challenges. Addressing these barriers and implementing students’ recommendations can enhance the credibility, accessibility and impact of evaluation systems. Contribution: The findings provide valuable insights for universities to develop ongoing strategies and targeted interventions to improve the implementation of SLEs, foster accountability and promote continuous enhancement of teaching and learning quality.